Class Ridden or Meritocratic? An Economic Analysis of Recent Changes in Britain - Fernando Galindo-Rueda; Anna Vignoles (Institute for the Study of Labor (IZA), 2003)
In a meritocratic society an individual's economic success is determined by their ability, not by their parents' socio-economic status. We assess whether meritocracy has increased in both the British education system and labour market. The richness of our longitudinal data enables us to look at the complex inter-relationship between social class, ability, education and labour market outcomes. In Britain the production of human capital (cognitive ability and education) has become less meritocratic and more influenced by social background. Whilst cognitive ability is an important determinant of labour market success, there is only mild support for an increase in its importance.
Keywords: J31; I20; 330; meritocracy; ability; human capital; social class; wages; Erwerbsstatus; Bildungsinvestition; Kognition; Soziale Schicht; Familiensoziologie; Bildungsertrag; Schätzung; Großbritannien